EFEKTIVITAS PELAYANAN MOBILE GOVERNMENT MELALUI APLIKASI LAYANAN TUNGGU (LAGU) OLEH DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU TAHUN 2020-2021 - Siagian, Anggi Loami; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The Layanan Tunggu Application is an application made to make it easier for the public to take care of population documents in the form of lost-KTP, Damaged-KTP and KTP-Berneedur/urgent. The process of implementing services through the LAGU application in 2020-2021 reaped many complaints from the public caused by obstacles experienced by users when accessing services through Layanan Tunggu Application. This study intends to formulate the effectiveness of mobile government services through the Layanan Tunggu application by Disdukcapil Pekanbaru City in 2020-2021. The research location is in Pekanbaru City, precisely at the Population and Civil Registration Office of Pekanbaru City. This research uses the theory of the effectiveness of mobile government services proposed by Jasin, namely program planning, implementation process, achievement / productivity results and community satisfaction. Data collection techniques through interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing or verification. The results showed that the effectiveness of mobile government services through the Layanan Tunggu application has not been implemented effectively. The implementation process is constrained by dependence on the central server and the limited availability of E-KTP stamps, causing the productivity of the Layanan Tunggu application service to be not optimal. However, in 2021, several obstacles can be overcome, namely the creation of a Backup server and a piece of paper in the form of a temporary E-KTP when the delay in E-KTP stamps. then, at the Disdukcapil Service Office in Pekanbaru City, there are still some officers who are not friendly in responding to questions / complaints submitted directly by users of the Layanan Tunggu Application Keywords: Effectiveness, Service, Mobile Government, E-KTP, Pekanbaru City